PORTABLE AND CONTINUOUS MONITORING DEVICES IN NEPHROLOGY: ENHANCING CLINICAL OUTCOMES AND PATIENT QUALITY OF LIFE THROUGH REAL-TIME ASSESSMENT AND PERSONALIZED TREATMENT APPROACHES - Candeia, Victor César Urquiza; Teixeira, Thalyta Alves; Destefani, Afrânio Côgo; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Portable and continuous monitoring devices have emerged as valuable tools in nephrology, offering significant benefits for patients and healthcare providers. This narrative review explores the current state of portable and continuous monitoring technologies in nephrology, focusing on their applications, clinical outcomes, and impact on patient quality of life. The methodology involves a comprehensive literature search of relevant databases, including Scopus, PubMed, and ScienceDirect. The results section is divided into subtopics, covering various aspects of portable and continuous monitoring devices in nephrology. These include improved dialysis monitoring, remote monitoring in peritoneal dialysis, continuous glucose monitoring, real-time glomerular filtration rate monitoring, wearable bioimpedance spectroscopy, and ambulatory blood pressure monitoring. Each subtopic presents the latest evidence, highlighting the potential of these technologies to enhance clinical decision-making, empowering healthcare providers with the tools to make confident and informed decisions, optimize treatment strategies, and improve patient outcomes. The discussion synthesizes the findings, addressing the implications for clinical practice, limitations, and future research directions. The review concludes by emphasizing the transformative potential of portable and continuous monitoring devices in nephrology, advocating for their wider adoption and integration into standard care protocols.